Study and Design for Cloud Call Center Architecture - Zhehong Tang; Qing Li; Shaomin Wang (Dianxin kexue)
A cloud call center architecture was presented and the call center platform cloud technology and business model were studied. The cloud call center application prospect and business trends were also described. A reference of call center platform cloud and technology development was provided for the operator.